5G mobile networks based on SDN concepts - Hicham, Magri; Abghour, Noureddine; Ouzzif, Mohammed (International Journal of Engineering and Technology, 2018)
With The rapid growth of mobile networks data and the emergence of the new services and applications, Mobile operators should provide a several solutions to cope with the challenges of the next 5G mobile networks and to reduce costs. For these reasons, SDN was proposed to be one of the key technology trends that will facilitate the required architectural agility needed in the next 5G mobile networks.Software Defined Networking (SDN) is the highly promising technology to provide innovation and enforce the main drivers in 5G mobile networks such as flexibility, suability, serviceâ€“oriented management and to reduce costs by the softwarization of the 5G Core networks functions.Thus, there is an immediate need to study the fundamental architectural principles of SDN, and to analyze the integration and application scenarios of this architecture into the next 5G mobile networks. In this paper, we present a survey on the most relevant research works on SDN concepts and SDN integration in mobile networks. We propose a SDN-based architecture for 5G mobile network; we give an over-view of SDN requirements and challenges for SDN integration in 5G, we address the benefits of IPv6 over SDN in 5G and finally we provide the benefits of SDN integration in 5G mobile networks.Â